2021
DOI: 10.1158/0008-5472.can-20-2275
|View full text |Cite
|
Sign up to set email alerts
|

Functional Determinants of Cell Cycle Plasticity and Sensitivity to CDK4/6 Inhibition

Abstract: Intrinsic or acquired resistance to clinically approved CDK4/6 inhibitors has emerged as a major obstacle that hinders their utility beyond ER+ breast cancer. In this study, CDK4/6-dependent and -resistant models were employed to identify functional determinants of response to pharmacologic CDK4/6 inhibitors. In all models tested, the activation of RB and inhibition of CDK2 activity emerged as determinants of sensitivity. While depleting CDK4 and 6 was sufficient to limit proliferation in specific resistance s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 53 publications
2
37
0
Order By: Relevance
“…This would suggest that the senescence phenotype is less dependent on the trigger and rather dependent on the cell line model. To expand on this, we asked whether the same trend in response to ABT-263 and SASP factors is seen for two other drugs described to induce senescence: (1) doxorubicin, a DNA intercalator and topoisomerase II inhibitor (Chang et al, 1999 ; Gewirtz, Cell Reports 36, 109441, July 27, 2021 Resource ll OPEN ACCESS 1999); and (2) cyclin-dependent kinase (CDK) 2/4/6 inhibitor PF-06873600 (next referred to as PF) (Kumarasamy et al, 2021;Pandey et al, 2020). Four cell line models (A549, HCT116, MCF7, Huh7) were selected based on the cancer type (lung, colon, breast, and liver), response to ABT-263, and expression of IL6.…”
Section: Gene Expression In Senescent Cancer Cells Evolves Over Time and Is Independent Of Senescence Triggermentioning
confidence: 76%
“…This would suggest that the senescence phenotype is less dependent on the trigger and rather dependent on the cell line model. To expand on this, we asked whether the same trend in response to ABT-263 and SASP factors is seen for two other drugs described to induce senescence: (1) doxorubicin, a DNA intercalator and topoisomerase II inhibitor (Chang et al, 1999 ; Gewirtz, Cell Reports 36, 109441, July 27, 2021 Resource ll OPEN ACCESS 1999); and (2) cyclin-dependent kinase (CDK) 2/4/6 inhibitor PF-06873600 (next referred to as PF) (Kumarasamy et al, 2021;Pandey et al, 2020). Four cell line models (A549, HCT116, MCF7, Huh7) were selected based on the cancer type (lung, colon, breast, and liver), response to ABT-263, and expression of IL6.…”
Section: Gene Expression In Senescent Cancer Cells Evolves Over Time and Is Independent Of Senescence Triggermentioning
confidence: 76%
“…Mechanistically, continuous activation of cell cycle signal is one of the predominant biological characteristics of malignant tumor progression, and anti-tumor drugs based on targeting cell-cycle regulators, such as CDK inhibitors, have been proved to be effective [ 42 , 57 ]. However, inherent or acquired resistance of cancer cells to CDK inhibitors has become a major obstacle to their clinical application [ 58 , 59 ]. Alternative strategies to modulate cell cycle regulators in cancer cells are therefore anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…As important mediators of the cell cycle, CDK2, CDK4 and CDK6 belong to the cell division cycle 20-related kinase family ( 20 , 21 ). Previous studies have shown that the expression levels of CDK2, CDK4 and CDK6 are often upregulated in various types of cancer, and are associated with tumorigenesis by interacting with other proteins ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%